GEOGRAPHICAL ELEVATION INFLUENCE TOWARD VOWEL SOUNDS OF BALINESE LANGUAGE IN TABANAN BALI (THE CASE OF PUJUNGAN AND BERABAN DIALECTS) - PUTRI, DEWA AYU DYAH PERTIWI (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Prosodic Features, Vowel Sounds, Balinese Language, Tabanan Dialect, Geographical Elevation, PRAAT Geographical elevation as one of environmental elements is thought for taking part in sounds production by affecting the rate of air pressure beneath human pharyngeal cavity through the rate of atmospheric air pressure. By this, investigating the influence of geographical elevation toward prosodic features of vowel sounds in Balinese language would be the aim of this research. To reach the aim, the researcher formulated two problems that question what prosodic features differences are found among Balinese vowel sounds which are produced by Pujungan and Beraban villagers, and what influences are given by geographical elevation toward the prosodic features. The research is conducted in phonetic aspect acoustically, since acoustic tendency is the essence of verbal language as Balinese language.The research used non-experimental quantitative design, specifically causal-comparative research. The sampling process was done in two villages in Tabanan regency, which were Pujungan (high elevation region) and Beraban (low elevation region). The samples (N=30 per village) were collected by purposive sampling in which the samples should be the native of each village who should utter 13 selected swadesh words which contain all of vowel sounds in Balinese language in a natural conversation. The vowel sounds would be measured by PRAAT to find out their acoustic features as the research data which indicate the rate of their prosodic features. Further, the data were tested by T-test (α 0.05), and compared.As results, the length of entire vowel sounds which were uttered by Pujungan villagers were found to be shorter than those which were uttered by Beraban villagers. Instead, the pitch and stress of vowel sounds which were uttered by Pujungan and Beraban villagers were found to be similar statistically. By this, it could be concluded that the lower the elevation, the longer sounds would be produced. However, since the pitch and stress in Pujungan and Beraban dialects were found to be similar, the influence of geographical elevation toward them could not be confirmed accordingly.A suggestion was given for future related researches to select sampling regions which have deeper elevation gap compared to the elevation gap between Pujungan and Beraban villages for resulting more significant difference, particularly for pitch and stress classes.